IMPACTO DE UTILIZACIÓN GENERALIZADA DE CONTRATOS DE CRÉDITO CON TASAS VARIABLES EN COSTA RICA: TRANSICIÓN A UN SISTEMA DE METAS DE INFLACIÓN - Villamichel Morales, Pablo (2013)
The dynamics of loan interest rates has a growing importance in the gradual implementation of the inflation-targeting scheme that began in 2006. Costa Rica is a bi-currency economy in which the majority of credit agreements granted by the Local Financial System have adjustable interest rates tied to a short-term interest rate, both in colones and in dollars. According to economic literature this type of contracts transfer signals form market interest rates to consumption and investment faster and more directly than fixed-rate contracts. Part of this effect is mitigated by the widespread use of floors on adjustable rate loans that generates nonlinearities in the transfer process from the reference interest rate to the actual rates paid by debtors. This alternative has not been studied in theoretical models and should be considered as a possible limitation to the effective use of the Monetary Policy Rate going forward.